2016
DOI: 10.1021/jacs.6b02968
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Layered Assemblies of Hydrogen-Bonded, Hexagonal Networks of C3-Symmetric π-Conjugated Molecules: A Potential Motif of Porous Organic Materials

Abstract: Hydrogen-bonded porous organic crystals are promising candidates for functional organic materials due to their easy construction and flexibility arising from reversible bond formation-dissociation. However, it still remains challenging to form porous materials with void spaces that are well-controlled in size, shape, and multiplicity because even well-designed porous frameworks often fail to generate pores within the crystal due to unexpected disruption of hydrogen bonding networks or interpenetration of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
170
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(176 citation statements)
references
References 63 publications
4
170
2
Order By: Relevance
“…Based on such analyses, CC3 would be predicted from its energy–structure landscape to be a robust tecton, 62 whereas CC1 would not. 129 More recently, the CSP approach was extended to extrinsically porous molecules, 68,138 such as the hydrogen-bonding frameworks developed by Mastalerz. 30 We showed that the energy–structure landscapes for such molecules can be complex: for example, a trigonal benzimidazolone was found to have at least four stable porous polymorphs with predicted densities in the broad range 0.4–1.25 g cm –3 and predicted surface areas ranging from 442 to 3230 m 2 g –1 .…”
Section: Energy–structure–function Mapsmentioning
confidence: 99%
“…Based on such analyses, CC3 would be predicted from its energy–structure landscape to be a robust tecton, 62 whereas CC1 would not. 129 More recently, the CSP approach was extended to extrinsically porous molecules, 68,138 such as the hydrogen-bonding frameworks developed by Mastalerz. 30 We showed that the energy–structure landscapes for such molecules can be complex: for example, a trigonal benzimidazolone was found to have at least four stable porous polymorphs with predicted densities in the broad range 0.4–1.25 g cm –3 and predicted surface areas ranging from 442 to 3230 m 2 g –1 .…”
Section: Energy–structure–function Mapsmentioning
confidence: 99%
“…Previously, the development of porous materials for CO 2 adsorption focused mostly on the design of new metal–organic frameworks (MOFs) 3842 , hydrogen-bonded organic frameworks (HOFs) 4349 , covalent–organic frameworks (COFs) 5055 , and polymer organic frameworks (POFs) 5659 . MOFs and HOFs, also known as self-assembled frameworks, were studied using single crystal X-ray analysis and then the available void space could be observed at the atomic level; many of them possess high surface areas and porosity and thus show a remarkable CO 2 sorption ability.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds Tp , T12 , T18 , and Ex were synthesized according to reported methods . STM experiments were performed with a NanoscopeIIIa (Veeco Metrology, USA) instrument with mechanically formed Pt/Ir (80/20) tips.…”
Section: Methodsmentioning
confidence: 99%
“…On this basis, recently, a series of C 3 ‐symmetric π‐conjugated planar molecules ( Tp , T12 , T18 , and Ex ; Scheme ) were synthesized to provide new ideas for advanced materials . The central cores of these molecules are designed with different side lengths; this is the main difference between the four molecules.…”
Section: Introductionmentioning
confidence: 99%